A new species, a new synonymy, a revised generic assignment and new records in some African and Palaearctic Aradidae (Hemiptera: Heteroptera) - Heiss, Ernst (Zootaxa, 2023)
The late Ludvík Hoberlandt left several specimens of African Aradidae (Hemiptera: Heteroptera) in the collection of the National Museum in Prague which were labelled as new synonyms or types of new species, but, however, the corresponding taxonomic acts and decisions have never been published. As a result of their examination, Hoberlandt’s ‘Aradus africanus n. sp.’ is identified as A. gracilipes Linnavuori, 1978, ‘A. nuristanicus n. sp.’ as A. betulae (Linnaeus, 1758), and ‘Aradus intermedius n. sp.’ is recognized as a new species, described here as A. congoensis sp. nov. (from the Democratic Republic of the Congo). Mezira lindemannae Kormilev, 1974, syn. nov., is synonymized with Brachyrhynchus abyssinicus Bergroth, 1895. The generic placement of Mezira amplicollis Linnavuori, 1978 in Brachyrhynchus Laporte, 1832 is confirmed. The status of ‘Carventus machadoi n. sp.’ (member of Burgeonia Schouteden, 1919; Angola) and ‘Neuroctenus arnoldi n. sp.’ (Zimbabwe), two additional putatively new species recognized by Hoberlandt, remains unresolved, pending the revision of the respective genera. The following new distributional records are given: Aradus gracilipes from Chad, Aradus betulae from Afghanistan, and Brachyrhynchus abyssinicus from Democratic Republic of the Congo, Guinea and Kenya.